Case Report: Successful treatment of guselkumab in a patient with verrucous psoriasis unresponsive to secukinumab - Zheng, Jianfeng; Yi, Xuemei; Shi, Yuling; Ding, Yangfeng (Frontiers in Immunology, 2025)
A 77-year-old Chinese male with a 10-year history of plaque psoriasis had recurrent episodes of symmetric hypertrophic verrucous plaques in the lower legs. The patient was monitored for the evolution of the disease over two years before he came to our attention. Because the lesions were resistant to topical glucocorticoids and vitamin D3 at another dermatological center, the patient was treated with secukinumab for one year. However, the verrucous lesions further worsened, and the patient visited the outpatient department of our hospital in March 2023. Treatment with guselkumab was started. It immediately attenuated the plaques of the trunk and limbs. Surprisingly, the verrucous plaques of both legs showed complete resolution in 6 months.